RECRUITMENT PRACTICES AND CRITERIA OF THE SUPPLIERS OF THE AUTOMOTIVE INDUSTRY - Daniela MIHAI; Mădălina BRUTU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2012)
The paper has as a purpose the analysis of the recruitment activity, from a theoretical and a practical point of view, at the level of a multinational company that carries on its activity in the automotive industry. In order to reach this purpose, we have studied the Romanian and foreign literature of the field and we have taken an in-depth interview to the human resources manager. The recruitment activity is extremely important for the automotive industry suppliers, especially at the level of the county of Argeş, because here we can find the greatest concentration of such companies. Because of the problematic economic and financial situation, at the level of the county of Argeş it is difficult to recruit in this industry. In order to be able to do it, the multinational companies have to manage their activity correctly and to design successful practices!